Collaborative creativity among undergraduate students as game creators during gamification in a university-wide elective course - Julia Ai Cheng, Lee; Lim, Ruxin; Fitri Suraya, Mohamad; Chan, K.G; Faizah, Masud (University of Wollongong Australia, 2023)
Collaborative creativity is an essential skill for unleashing university students’ skills in team building during complex problem-solving. The aim of this descriptive quantitative research was to examine undergraduate students’ perspectives regarding their collaborative creativity experience as game creators for a gamification group assignment within a university-wide elective course on learning disabilities. The Assessment Scale of Creative Collaboration (ASCC) questionnaire was completed by 14 students. The results provide insightful perspectives by undergraduate students regarding their experience in collaborative creativity during game creation. The findings from the closed-ended questions of the ASCC demonstrate that most of the students valued the diversity of knowledge and skills of their team members, shared different ideas, adapted their ideas and practices according to the project difficulties, trusted their team members, co-constructed the game together, overcame conflicts in positive ways, developed multiple versions of their game, and coordinated well for their team project. Data from the open-ended questions of the ASCC, which provided detailed but nuanced perspectives of the students, were analysed thematically. Three main themes were identified: the positive aspects of gamification, the constraints related to the gamification project, and teamwork and collaborative problem-solving approaches. This study provides evidence on the feasibility of game creation that is embedded within gamification group projects for fostering collaborative creativity among undergraduate students. Gamification has the potential in supporting the acquisition of 21st century learning and innovation skills in higher education. Implications of the application of gamification in higher education are discussed.